Making the most of person-centred education by integrating flipped and simulated teaching: An exploratory study. (November 2017) - Saunders, Annette; Green, Rosy; Cross, Merylin
Abstract: Preparing a person-centred nursing workforce to work in diverse settings is a global health priority. Nursing students' first placement experience is a key transitional moment that shapes professional understanding and motivation to become a nurse. This paper reports the outcomes of combining flipped and simulated learning to enhance nursing students' understanding of person-centred care, the professional nursing role and preparation for placement. The study design was exploratory, the setting, an undergraduate nursing program in an Australian University. Participants included first year nursing students, academic tutors and clinical facilitators. Data collected via survey, semistructured interviews and focus group discussion were analysed descriptively and thematically. Over 90% of students surveyed considered the unit structure, content and resources prepared them well for placement. Pre-class preparation and simulated tutorial activities facilitated student engagement and knowledge translation. Students, tutors and clinical facilitators valued the person-centred approach. Tutors considered the unit materials and focus enhanced students' professional understanding. Clinical facilitators deemed students well-prepared for placement. These results from multiple perspectives, though limited, support combining the flipped classroom and person-centred simulation in nursing education as a strategy to prepare students for clinical placement, translate person-centred values into practice and promote professional understanding and role socialisation. Highlights: The flipped approach to learning fostered student engagement and role transition. Linking flipped and simulated learning promoted higher-order knowledge translation. Person-centred simulation prepared nursing students well for their first placement. Students, tutors and facilitators valued students' becoming a person-centred nurse. Exposing students to varied simulated settings enhanced professional understanding.